2023
DOI: 10.9734/ejmp/2023/v34i71146
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Costus speciosus and Determination of Antioxidant Potential Using DPPH Method: A Review

Athoya Delarosa,
Ryan Proxy Hendrawan,
Eli Halimah

Abstract: Medicinal plants are garnering widespread interest in scientific circles due to their consistent pharmacological activities, which make them beneficial in the treatment of a variety of ailments. Costus speciosus, commonly known as crepe ginger, is an herbaceous plant native to Mexico that belongs to the family Costaceae (zingiberaceae). Creep Ginger is known to have many medicinal effects, such as antioxidant, anti-inflammatory, and potential antidiabetic activities. The aim of this review was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…C. speciosus is a medicinal herb in India with many pharmacological properties due to its powerful antioxidant activity [54,55]. Research demonstrated that costus has the potential to lower WBC count while boosting ICAM adhesion factor levels.…”
Section: Costus Speciosusmentioning
confidence: 99%
“…C. speciosus is a medicinal herb in India with many pharmacological properties due to its powerful antioxidant activity [54,55]. Research demonstrated that costus has the potential to lower WBC count while boosting ICAM adhesion factor levels.…”
Section: Costus Speciosusmentioning
confidence: 99%
“…Natural antioxidants can be single pure compounds/isolates, combinations of compounds, or plant extracts. The secondary metabolites, polyphenols, are the most common phyto-antioxidants [23]. Polyphenols have benzene rings with attached -OH groups which determine the antioxidant activity based on their number and position [24].…”
Section: Antioxidantmentioning
confidence: 99%